Սուրիոյ քրիստոնեայ այլադաւան հայերը եւ անոնց ազգային ինքնութեան խնդիրը - Յակոբ Չոլաքեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена проблеме гетеродоксальных армян Сирии, не являющихся прихожанами Армянской Апостольской, Армянской Евангелической и Армянской Католической церквей. This article considers the part of heterodox Syrian Armenians, who do not belong to the Armenian Apostolic, Armenian Evangelical and Armenian Catholic communities.
Keywords: Armenian church; Christianity; Christian Denominations